A Comparative Study of Physical Fitness Levels Among Junior High School Students in Rural and Urban Areas - M. Ilham Ramadhan Suarlam; Muh Adnan Hudain; Jamaluddin Jamaluddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Physical fitness is a fundamental indicator of adolescent health, yet geographic disparities often create significant gaps in fitness achievement. This study aims to analyze and compare the physical fitness levels of junior high school students in rural and urban areas within the Polewali Mandar Regency. Using a quantitative descriptive approach with a comparative survey design, the study sampled 60 students from four schools: Junior High School 1 Polewali, Junior High School 1 Anreapi, Junior High School 1 Wonomulyo, and Junior High School 4 Wonomulyo. Data were collected using the Indonesian Student Fitness Test (TKSI) Phase D, covering hand-eye coordination, sit-ups, standing broad jumps, T-tests, and Bleep tests. The findings reveal a significant difference in physical fitness between the two groups. Although both cohorts fall within the